India's foreign policy: retrospect and prospect/edited by Sumit Ganguly (New Delhi, 2013)
This book provides a fairly comprehensive account of the evolution of India's foreign policy from 1947 to the present day. It is organized primarily in the form of India's relations with its neighbours and with key states in the global order. All the chapters in this volume utilize the level of analysis approach, a well-established conceptual scheme in the study of international politics in organizing the substantive cases. They provide crisp and lucid accounts of its developments in various parts of the world. The book is significant because there are no other viable edited volumes on the evolution of Indian foreign policy. Each chapter follows a common conceptual framework using the level of analysis approach. This framework looks at the evolution of India's foreign policy from the standpoints of systemic, national, and decision-making perspectives. In the introductory chapter, the editor carefully spells out the intellectual antecedents of the level of analysis framework in str
Keywords: "Foreign Policy-India, International relation, Ganguly, S"